2002
DOI: 10.1096/fj.02-0537fje
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TRAIL and its receptors in viral hepatitis

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is able to kill a broad spectrum of tumor cells but appears to be nontoxic to most normal cells. Because there are conflicting data about the hepatotoxicity of TRAIL, we investigated the physiological function of TRAIL and its receptors in the liver. Hepatocytes are sensitive for FasL- and TRAIL-mediated apoptosis in vitro, but TRAIL induces no apoptosis in healthy livers in vivo. Using mouse models of adenoviral hepatitis and livers of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
105
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 42 publications
(60 reference statements)
8
105
0
1
Order By: Relevance
“…To determine whether innate immune cells were required for tumour clearance, mice bearing subcutaneous hepatocarcinomas harbouring the conditional p53 shRNA were treated with gadolinium chloride (a macrophage toxin) 19,20 or neutralizing antibodies to suppress neutrophil or natural killer cell function 20,21 , and monitored for tumour regression following Dox treatment. All three treatments significantly delayed tumour regression following p53 reactivation (Fig.…”
mentioning
confidence: 99%
“…To determine whether innate immune cells were required for tumour clearance, mice bearing subcutaneous hepatocarcinomas harbouring the conditional p53 shRNA were treated with gadolinium chloride (a macrophage toxin) 19,20 or neutralizing antibodies to suppress neutrophil or natural killer cell function 20,21 , and monitored for tumour regression following Dox treatment. All three treatments significantly delayed tumour regression following p53 reactivation (Fig.…”
mentioning
confidence: 99%
“…Adenovirus preparation and viral plaquing were performed as described (5,6). AdFasL was administered via tail vein in a dose of 6.25 ϫ 10 7 pfu͞g of body weight.…”
Section: Adenovirus Preparation and In Vivo Infection Experimentsmentioning
confidence: 99%
“…Mice injected with agonistic Fas (CD95) antibody rapidly develop ALF and die within hours (3). In animal models of acute viral hepatitis, apoptosis of hepatocytes is mediated by death receptors such as Fas (CD95), tumor necrosis factor (TNF)␣, and TNFrelated apoptosis-inducing ligand (4)(5)(6), and several studies in humans showed that apoptosis of hepatocytes in Wilson's disease, toxic liver damage, and viral hepatitis is triggered through death receptors (7,8). Consequently an attractive strategy to treat patients with ALF would be to inhibit death receptor-mediated apoptosis to maintain liver function and save the organ.…”
mentioning
confidence: 99%
“…46 In hepatocytes, TRAIL-mediated apoptosis in vivo has been shown to depend on triggering through viral infection. 47 Thus, endogenous overexpression of TRAIL seems to enable the organism to selectively eliminate virally infected hepatocytes. TRAIL and its receptors in mouse hepatitis models display up-regulation in adenovirus infection, and liver cells have been demonstrated to be sensitized toward TRAIL-induced cytotoxicity by HBV replication in vitro.…”
Section: Function Of Trail and Its Receptors In Liver Diseasementioning
confidence: 99%
“…In patients with chronic hepatitis B, HBV infection may increase serum TRAIL, 48 and HBV-infected hepatocytes can be killed by up-regulated TRAIL. 47 Recently, Higuchi et al [49][50][51] reported that bile acids up-regulate TRAIL-R2 expression, and Zheng et al 52 demonstrated the essential contribution of TRAIL in concanavalin A-induced and Listeria-induced liver injury, indicating that TRAIL is also an important mediator of apoptosis in nonviral liver disease. Surprisingly, Mundt et al 53 recently reported that TRAIL expression in virally infected livers of mice not only induced apoptosis of infected hepatocytes but also led to steatosis, a characteristic feature of liver diseases such as chronic hepatitis C, alcoholic liver disease, and nonalcoholic steatohepatitis.…”
Section: Function Of Trail and Its Receptors In Liver Diseasementioning
confidence: 99%